Social Aspects of Cognitive Linguistics: Studying Language Attitudes and Identity - Kulichenko, A. K.; Avchinnikova, H.; Polyezhayev, Yu.; Maksymova, A.; Romanchuk, S.; Куліченко, Алла Костянтинівна (My University, 2025)
The analysis of language attitudes seeks to elucidate various dimensions of linguistic functioning, particularly where the social dimensions of discourse are manifest, such as lexical encoding, interaction positioning, and discursive strategies. It also considers elementsaligned with cognitive models that shape language use in specific contexts, cultivated through socialization and the formation of social identity. Linguistic identity, a multifaceted construct, encompasses both linguistic and cultural knowledge and plays a key role in shaping personality. This study examines the linguistic identity of plurilingual students from various Ukrainian higher education institutions, assessing how plurilingualism impacts their identity. Using qualitative analysis of survey data from 31 students collected in autumn 2023, the study explores themes such as the influence of linguistic environments on plurilingualism, language attitudes, and self-identification. The findings indicate that all languages spoken by an individual contributeto shaping their linguistic identity, with self-identification as bilingual or plurilingual influenced by personal language proficiency and relevant language environments. The results support the idea that linguistic identity evolves over time, highlighting the dynamic nature of language and identity in response to varying social contexts.
Keywords: cognitive linguistics; language perception; cultural differences; linguistic anthropology; language interaction; sociolinguistics